Emotional and Cognitive Experiences of Pregnant Women Following Prenatal Diagnosis of Fetal Anomalies: A Qualitative Study in Iran - Morvarid Irani; Talat Khadivzadeh; Seyyed Mohsen Asghari Nekah; Hosein Ebrahimipour; Fatemeh Tara (International Journal of Community Based Nursing and Midwifery, 2019)
Background: Pregnant women are often ill-prepared for the health of their unborn child in the case of abnormal findings, and experience several difficulties following the detection of fetal anomalies. Therefore, this study was conducted to explore the emotional and cognitive experiences of pregnant women following prenatal diagnosis of fetal anomalies in Mashhad, Iran. Methods: This qualitative conventional content analysis study was designed through two referral centers for fetal anomaly. The data were collected from April 2017 to January 2018 in Mashhad (Iran) through individual semi-structured in-depth interviews, from 25 pregnant women with a prenatal diagnosis of fetal anomalies. Results: Four categories and 10 subcategories emerged. Category one, grief reactions during the time of diagnosis, contained two subcategories: shocked and panicked, and distressed and disbelieved.Category two, perinatal loss through a pregnancy termination, contained four subcategories: guilt and shame during pregnancy termination, loss of their expected child, suffering and emotional distress process, and unmet needs by health professionals. Category three, fears of recurrence in future pregnancies, had two subcategories: worried about inadequate prenatal care in the future pregnancies and worried about abnormal fetus in next pregnancies. Finally, Category four, a dilemma between hope and worries contained two subcategories: hope for normality and worried about future. Conclusion: It is important to monitor emotional reactions of women following prenatal anomaly diagnosis. So, training clinicians and health-care professionals for proper response to grief reaction in post therapeutic abortion is essential.